Cognitive function following pulmonary rehabilitation and post-discharge recovery from exacerbation in people with COPD. (January 2021) - France, Grace; Orme, Mark W.; Greening, Neil J.; Steiner, Michael C.; Chaplin, Emma J.; Clinch, Lisa; Singh, Sally J.
Abstract: Background: Cognitive impairment (CI) is prevalent in COPD and is associated with poor health-related quality of life. Recovery of cognition following an acute exacerbation of COPD (AECOPD), the impact of CI on pulmonary rehabilitation (PR) uptake and the effect of PR on CI are not fully understood. Methods: This 6-week prospective study analysed 67 people with stable COPD symptoms who completed PR (PR group) and the recovery of 45 people admitted for AECOPD (AECOPD group). All participants were assessed for cognitive function (Montreal Cognitive Assessment [MoCA]), health status (COPD Assessment Test, Chronic Respiratory Questionnaire), lower extremity function (Short Physical Performance Battery), and psychological well-being (Hospital Anxiety and Depression Score). Follow up assessments were carried out after a 6-week recovery post-discharge in AECOPD group and after PR in the PR group. Results: AECOPD group showed no improvement in MoCA following a 6-week recovery post-discharge (Δ-0.8 ± 3.2, p = 0.205), despite improvements in all other clinical outcomes. PR uptake among the AECOPD group was not associated with the presence of CI (p = 0.325). Participants in the PR group with CI at baseline showed a significant improvement in MoCA score following PR (Δ1.6 ± 2.4, p = 0.004). Conclusions: Cognition does not improve following 6-week recovery post-AECOPD, and CI may influence patients' response to PR referral as an inpatient. PR improves cognition in people with stable COPD symptoms and CI. People with AECOPD should be actively encouraged to attend PR irrespective of mild-moderate cognition but may require additional support or opportunities to take part. Highlights: Cognition does not improve following a 6-week recovery post-exacerbation of COPD. Pulmonary rehabilitation (PR) may be beneficial for those with cognitive impairment. Cognitive impairment should not be a barrier to referring patients to PR.